Development of Satellite Propagation Effects Tool For Ku-Band, Ka-Band And Q/V-Band Links - Ahmad Hambali, Nor Azura Malini (2005)
The thesis presents Graphical User Interfaces (GUIs) to analyse satellite propagation effects for Ku-band, Ka-band and QN-band links by using Matlab programming languages. The Matlab-based tool allows simulation to be carried out in the step and run modes. The Graphical User Interface (GUI) is a powerful, unique utility and programming interface, usable for research and simulation in the optimisation of microwave signal propagation. The GUIs gives easy access to analyse rain attenuation, cloud attenuation and fog attenuation. These software development tools are a set of Matlab solvers, graphical, computational utilities for quadratic, polynomial and regression programming. The GUIs may also be used as a preprocessor to generate Matlab code for stand-alone execution. Once the software tools for satellite propagation effects on Ku-band, Ka-band and QN-bands links GUIs is launched, user can enter input parameter values (frequency, elevation angle, temperature, visibility, cloud cover, rainfall, e.t.c) in text control to analyse the propagation impairments. In this thesis, the characteristics of the reliable design of satellite communication systems operating at frequency above 10 GHz, Ku (12.5 - 18 GHz), Ka (26.5 - 40GHz) and QN (40 - 50 GHz) band were examined. Rain attenuation, cloud attenuation and fog attenuation are the sources for fading propagation effects in these bands frequency. Analytical and ITU recommendations models were used to predict output attenuation for this analysis. However, the effects on satellite systems operating in the Ku, Ka and QN band essentially depends on the propagation characteristics of the transmission medium. The NOAA ((National Oceanic and Atmospheric Administration) satellite data 2003, which were obtained from the Malaysian Meteorological service, were used in this analysis for area of interest Subang (elevation angle 36.54'), Alor Setar (elevation angle 34.97'), and Batu Embun (elevation angle 37.25'). The rain attenuation due to rainfall depends on the rain rate (mrnlhr) distribution at the 0.01% probability as main the input. At the Ku, Ka and QN-bands frequencies, rain is a dominant source of attenuation. Thunderstorm activities were found to give large effect on the rain rate values during raining condition. Cloud attenuation is a function of cloud temperature integrated cloud liquid water content (g/m3) along propagation path. For fog attenuation, visibility and temperature become main meteorological input function along propagation path analysis at the earth station site. Cloud and fog attenuation, which have been neglected at the lower frequencies band, can significantly limit the performance of high frequencies band satellite systems. However, in recent years, higher frequencies are gradually being used for satellite communications in order to avoid congestion in the traditional low bands (S, L, C and X) frequencies and can be used for high quality satellite service. Unfortunately increasing operating frequency from Ku-band to Ka-band and QN-band will increase the attenuation level and hence, reducing performance of the satellite.